Tri-reforming of methane over a highly-dispersed hydroxyapatite-supported nickel catalyst - Pham Xuan-Huynh; Minh Doan Pham (E3S Web of Conferences)
Tri-reforming of methane is a promising process to produce synthetic gas via the reforming of methane simultaneously with three different oxidants: water vapor, carbon dioxide and oxygen. The thermodynamic aspect of this reaction requires high reaction temperatures (above 700 °C) to reach high methane conversion, while the kinetic aspect requires a solid nickel-based catalyst to reach high reaction rates. Consequently, the solid catalyst used in TRM is exposed to several risks of deactivation, and the development of a performing catalyst is a great challenge for TRM process. In this work, it has been demonstrated that hydroxyapatite (HAP) supported nickel catalyst prepared by ion exchange / ultrasonic vibration led to the formation of nickel nanoparticles and sub-nanoparticles on the HAP support surface, and the resulting catalyst showed very good catalytic performance.